QR CODE BASED SMART CARD INNOVATION FOR INDEPENDENT MATHEMATICS TRAINING AT SDN 5 KEDATON, BANDAR LAMPUNG CITY - Afiyah Diyanah; Chairunnisa (Innovate Inovation Teaching And Learning, 2025)
The proliferation of digital technology in education necessitates innovative learning media that seamlessly integrate technology with conventional pedagogical approaches. This research attempts to develop and evaluate the efficacy of QR code-based smart cards as an autonomous mathematics practice medium. The methodology employed a Research and Development (R&D) framework using the ADDIE model, encompassing 120 secondary school students as participants. Data collection was conducted through achievement tests, motivation questionnaires, and learning observation protocols. The smart cards were ingeniously designed with QR code technology that establishes connectivity between physical content and digital platforms containing interactive exercises, instructional videos, and automated assessment systems. Research findings demonstrate substantial enhancement in student learning motivation by 78% and mathematics achievement by 65% ​​compared to conventional methodologies. Analysis reveals that 92% of students experienced higher motivation attributed to accessibility and interactivity affordances. The integrated analytics system empowers educators to monitor student progress in real-time while delivering timely pedagogical feedback. This innovation proves effective in cultivating adaptive and engaging learning environments. QR code-based smart cards emerge as an innovative solution for enhancing mathematics education quality in the digital era while supporting effective autonomous learning implementation.